A Quantitative Analysis of DEI Program Strength and Female Executive Representation in Fortune 500 Companies - Bora, Gaargi (Advances in Social Sciences Research Journal, 2025)
Despite decades of public DEI commitments, women remain underrepresented in executive-level leadership within Fortune 500 companies. This study uses a quantitative analysis to investigate if improved DEI initiatives correlate with increased female representation in executive and C-suite roles in seven general merchandisers. Companies were assigned DEI Program Strength Scores (1-5) based on mentorship, training, and promotion transparency activities and benchmarked against weighted representation scores targeted at C-suite levels. Results indicated no relationship between DEI scores and female leadership representation (R² = 0.04, p = 0.66), suggesting that publicly stated DEI programs by themselves are weak indicators of advancement outcomes. Instead, variation between companies implies that structural and cultural factors—i.e., levels of mentorship access, leadership accountability, and organizational bias—are more likely to have a profound impact. These findings support the continued gap between DEI rhetoric and representation outcomes and affirm the need for systemic, measurable change toward facilitating equal opportunity for women to advance in corporate leadership roles.